Parametric modelling of walls: Visual permeability to urbanity - Teixeira, R.; Lopes, J. V.; Paio, A.; Guerreiro, M. R. (Anais do XIX Congresso da Sociedade Ibero-americana de Gráfica Digital 2015, 2015)
Visually impermeable boundaries growth of residential multifamily buildings in Boa Viagem (Recife-BR) increases urban environment of buildings that ignore streets and pedestrians. Minimizing it, without disturbing the private use, this work consists in modelled walls defined by cobogós (typical hollow elements of the region), manipulated to guarantee some privacy and visual permeability at the same time. With Space Syntax tools and support, part of the neighborhood is analyzed both in its actual configuration, and after the post-supposed interventions. Analysis supported the design work decisions, making increase of visual range in public spaces possible, as a way of stimulate the urbanity.